2017
DOI: 10.1002/asia.201700686
|View full text |Cite
|
Sign up to set email alerts
|

Strongly Luminescent Cyclometalated Gold(III) Complexes Supported by Bidentate Ligands Displaying Intermolecular Interactions and Tunable Emission Energy

Abstract: A series of charge-neutral Au complexes, which comprise a dicarbanionic C-deprotonated biphenyl ligand and bidentate ancillary ligands ([Au(C^C)(L^X)]; L^X=β-diketonate and relatives (O^O), quinolinolate and relatives (N^O), and diphosphino (P^P) ligands), were prepared. All the complexes are emissive in degassed CH Cl solutions and in thin-film samples with Φ up to 18 and 35 %, respectively, except for 5 and 6, which bear (N^O)-type ancillary ligands. Variation of the electronic characteristics of the β-diket… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 110 publications
1
35
0
Order By: Relevance
“…Thanks to a low turn‐on voltage of 2.4 V, high power efficiency of 99.4 lm W −2 was achieved in the 2 device at the dopant concentration of 8 wt%. To the best of our knowledge, this is the highest value among Au‐OLEDs . The device performance and operational lifetime of OLEDs based on 6 have been evaluated by Samsung with industry standard (see the Supporting Information for details).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thanks to a low turn‐on voltage of 2.4 V, high power efficiency of 99.4 lm W −2 was achieved in the 2 device at the dopant concentration of 8 wt%. To the best of our knowledge, this is the highest value among Au‐OLEDs . The device performance and operational lifetime of OLEDs based on 6 have been evaluated by Samsung with industry standard (see the Supporting Information for details).…”
Section: Resultsmentioning
confidence: 99%
“…However, contrary to iridium that has been extensively used in organic light‐emitting diode (OLED) technology, examples of gold OLED with practical interests are scarce. The first example of gold OLED was reported by Ma and Che in 1999 with inferior performance, and device performance has been improved in recent years exploiting luminescent cyclometalated Au(III) complexes . Due to the electrophilic nature/relatively high reduction potential of Au(III) ion, the luminescent excited states of Au(III) complexes are usually ligand centered with little metal character, resulting in long triplet emission lifetimes, thereby posing significant challenges to achieve high performance OLEDs with low efficiency roll‐off at high luminance and driving voltage.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the findings of To ste, [35] Bourissou [36] and Bertrand [37] on the oxidative addition of biphenylenet os everalA u I species, the transmetalation of stannoles is the method of choice for the preparation of cyclometalated biphenyldiyl Au III complexes. [34,38] Thus, we anticipated the corresponding 4-substituted stannoles 5 would be equallyu seful for the preparation of non-palindromic (C^C^D)c omplexes of gold.…”
Section: Retrosyntheticc Onsiderationsmentioning
confidence: 99%
“…This approach was used by different groups for the preparation of luminescent gold(III) complexes. [30][31][32] In 2015, Nevado and co-workers 33 described the nonpalindromic 34 (C^C^N) analogue of the (C^N^C) pincer and proved the corresponding gold(III) complexes to outperform most palindromic congeners in regard of emission quantum yields. 35 In subsequent reports it was shown that the [(C^C^N)Au(III)] complexes differentiate from the palindromic counterparts with respect to chemical properties as well.…”
Section: Introductionmentioning
confidence: 99%